2012
DOI: 10.1007/s10765-012-1231-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Diffusivity Measurements of Conductive Composites Based on EVA Copolymer Filled With Expanded and Unexpanded Graphite

Abstract: In this research, the thermal diffusivity of composites based on ethylenevinyl acetate (EVA) copolymer filled with two kinds of reinforcement graphite materials was investigated. The reinforcement graphite fillers were untreated natural graphite (UG) and expanded graphite (EG). Composite samples up to 29.3 % graphite particle volumetric concentrations (50 % mass concentration) were prepared by the meltmixing process in a Brabender Plasticorder. Upon mixing, the EG exfoliates in these films having nanosized thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] One way to improve the thermal and electrical conductivity, as well as the viscoelastic behavior and mechanical properties, of these materials is to combine polymer matrices with highly conductive fillers. However, there are many industrial applications such as circuit boards, heat exchangers, electromagnetic shielding devices, antistatic plastics, packaging, and others that require an improvement in both the thermal and electrical conductivity of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] One way to improve the thermal and electrical conductivity, as well as the viscoelastic behavior and mechanical properties, of these materials is to combine polymer matrices with highly conductive fillers. However, there are many industrial applications such as circuit boards, heat exchangers, electromagnetic shielding devices, antistatic plastics, packaging, and others that require an improvement in both the thermal and electrical conductivity of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Tlili et al 2 reported on the thermal and electrical conductivities of EVA14 filled with EG and unexpanded graphite (UG). Some theoretical equations have been proposed to predict the electrical and thermal conductivities of polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results show little change in thermal stability with increasing EG content and very little was reported on changes in the mechanical properties. Tavman et al and Tlili et al both compared the electrical properties of EVA (with 14 wt % vinyl acetate) containing respectively EG and unexpanded graphite. George et al reported a comprehensive study on reinforcement of EVA by differently treated naturally occurring graphites.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivities of EVA/UG and EVA/EG composites were measured by four-point method [10], the results of the measurements are given in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%